Peran BPD dalam melaksanakan Fungsi Pengawasan Kepala Desa di Desa Sarimulyo Kecamatan Ngawen Kabupaten Blora - Pambudi, Bagus; ., Hermini; Astrika, Lusia (Journal of Politic and Government Studies, 2014)
AbstractThis study aims to explain the role of the Village Consultative Board exercises oversight of the village chief in the village of the District Sarimulyo Ngawen Blora. Explaining how the supervision by the Village Board of the Village Government Consultative related to the case experienced by the village head Sarimulyo.The study is descriptive - analytical namely the type of research that aims to describe the symptoms as well analyze the symptoms using a qualitative approach. Subjects were Consultative Body (BPD) Sarimulyo Village, Village Government Sarimulyo, the village community resilience (LKMD) Sarimulyo Village, Community Leaders, Religious Leaders and representatives of villagers Sarimulyo specified. Data were collected by means of interviews, observation, documentation and analysis of literature relevant to this research.Based on the survey results revealed that the role of the Consultative Body (BPD) Sarimulyo village in performing their duties and functions are already well underway. Likewise Sarimulyo village government has been run in accordance with the Purposes and Functions available. However, in the course of the Village Head experiencing problems related to financial abuse village. These issues are a private matter Village head but a common problem for development in the village of Sarimulyo be hampered.Based on the case experienced by the village head can be seen that the performance is still not up to the village government as a violation of existing regulations. Neither the Village Consultative Board performance is not maximized, especially in terms of supervision. Inhibiting factors in the supervision carried out by the Village Consultative Body is cooperation and coordination between the Agency Consultative not maximized village with village government.Keywords: Role of Village Consultative Body (BPD), Village Government, Oversight